Effect of Bitter kola seed supplemented diet on Ageing, cholinesterase activities and redox status in Drosophila melanogaster model (African Journal of Biomedical Research, 2022)
This research evaluated the effect of bitter kola (Garcinia kola) seed on ageing and ageing-related biochemical modulations such as critical neural enzyme activities and oxidative stress makers in Drosophila melanogaster. Experimental flies were fed diet supplemented with Bitter kola (BK) throughout their life span. Treated flies were also homogenised 10-days post treatment and assayed for the activities of cholinesterase and catalase, reactive oxygen species (ROS), and malondialdehyde (MDA) contents. An LC/MS/MS phenolic analysis, as well as reducing property of BK seed was also determined. Results showed that flies raised on diet supplemented with BK seed exhibited significantly improved lifespan, locomotor performance and amelioration of impaired biochemical markers of ageing when compared with control. BK seed also modulated activities of cholinesterase. The LC/MS/MS analysis revealed abundance of Garcina bioflavonoids. Therefore, BK seed could be considered as a potential functional food candidate for reducing ageing and ageing-related biochemical impairments.